SMALL AREA ESTIMATION UNTUK PEMETAAN KEMISKINAN DI KABUPATEN DEMAK - Moh. Yamin Darsyah; Setia Iriyanto; Iswahyudi Joko S (Universitas Muhammadiyah Semarang, 2014)
Small area statistic is very interested in various fields at present. Estimation of small area is needed to obtain information on a small area, such as the scope of the district, subdistrict, or village. Such information becomes very important with the development of regional autonomy in Indonesia because it can be used as reference to construct a system ofplanning, monitoring, and other government policies without the cost of large to collect the data itself. The method being developed to predict small area statistics is the estimation of small area (small area estimation). Estimation for small areas in this study is applied to estimate poverty mapping of distric level in Demak. The result of poverty mapping in demak shows that population density become dominan factor poverty in some areas of demak.